Fertility Decline in Botswana 1980-2006 : A Case Study - World Bank (World Bank, Washington, DC, 2017)
Botswana has had a stable democratic government and good governance since independence in 1966. With a sustained high average economic growth (about 9 percent) fueled by the diamond mining industry, it is the only country in Africa listed among the 13 'economic miracles' of the world for 1960-2005. The total fertility rate remains high in Sub-Saharan Africa, with 25 countries showing a rate greater than 5.0. In contrast, Botswana experienced the greatest fertility decline in the region during 1980-2006, with the total fertility rate decreasing from 7.1 in 1981 to 3.2 in 2006. The Botswana national family planning program, judged the strongest in Africa, contributed to this decline. The government strongly committed to meeting family planning needs, integrated maternal and child health/family planning (MCH/FP) and sexually transmitted infection (STI) services in 1973. The government spends about 18 percent of its total budget on health, a higher proportion than the Abuja declaration's target of 15 percent.